High Moral Distress in Clinicians Involved in the Care of Undocumented Immigrants Needing Dialysis in the United States (Mary Ann Liebert, 2021)
Purpose: To understand clinicians' perspectives on dialysis care of undocumented immigrants. Methods: A 21-item Internet-based survey using Survey Monkey? was sent to 765 physicians and nurses at a safety-net hospital located in Indianapolis, IN. Moral distress thermometer score was used to assess moral distress (MD). Participants were asked to rate their MD regarding five ethically challenging clinical situations: (1) frail patients with multiple comorbidities and poor quality of life, (2) patients with dementia, (3) a noncompliant patient with frequent emergency room (ER) visits, (4) violent patients with potential harm to others, and (5) undocumented immigrants receiving emergent dialysis only. Key Results: There were 299 of 775 participants (38.5% response rate) who completed the survey; 49.5% were physicians. Nearly half (48%) reported severe MD and 33% reported none to mild. In adjusted ordered logistic regression, females had significantly higher odds of MD (odds ratio [OR]=2.12, CI 1.03?4.33), and nurses had lower MD than fellows/residents (OR=0.14, CI 0.03?0.63). Over 70% of respondents attributed their distress to suffering of patients due to inadequate dialysis and tension between what is considered ethical and the law allows or forbids; 78% believed the patients' quality of life to be worse than those who receive routine hemodialysis. Among nephrologists, caring for these patients led to MD levels like that of dealing with a violent dialysis patient. Conclusions: Emergent-only dialysis causes significant MD in clinicians. Legal and fiscal policies need to be balanced with the ethical and moral commitments of providers for ensuring standard of care to all.